Blue Biotechnology - He, Ning.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Blue Biotechnology is an open access, peer-reviewed journal featuring studies that cover all areas of applied research and biotechnology involving marine microorganisms (microalgae, bacteria and fungi), algae and invertebrates. Aspects of basic biological research, such as evolution, phylogeny and taxonomy, ecology and metagenomics, cellular and molecular biology, are considered only when they are relevant to biotechnology and support translational research. The vision for Blue Biotechnology is to contribute to the advancement of blue bioeconomy and the sustainable management and protection of oceans, fisheries, and coastal and marine environments. The main areas in scope are, but not only limited to: Bioproduction from aquatic biomass, such as food, feed, nutraceuticals, pharmaceuticals, cosmetics, energy, packaging, materials. Biotechnology, synthetic biology, and genetic and metabolic engineering for aquaculture Environmental aspects affecting marine biotechnology and bioproduction Development of marine biological resources and biodiversity Aspects of pathology and diseases related to marine biotechnology affecting human health Policy issues, life cycle assessments, and debates A key aim of Blue Biotechnology is to promote the visibility and reach of valid, diverse, and innovative research. While the main focus remains on research and reviews of wide applicability and relevance, the journal is also open to consider confirmatory research, short communications, data analyses and discussions, local studies of interest for specific regions, and case studies where the authors are able to show meaningful relevance to the broader discussion around key topics in marine biotechnology. Blue Biotechnology aims to highlight innovations that promote clean water and sanitation, sustainable cities and communities, life below water and life on land, according to the Sustainable Development Goals framework. Furthermore, the scope and the research published in Blue Biotechnology aims to resonate with the principles of Green Chemistry, particularly with the focus on safer solvents and reactions, energy efficiency, renewable feedstocks, degradation after use, and avoidance of chemical derivatives.
Keywords: Biotechnology; Environmental engineering; Biotechnology; Bioremediation; Freshwater ecology; Marine ecology; Renewable energy sources; Microbiology; Plant biotechnology; Biotechnology; Environmental Engineering/Biotechnology.; Freshwater and Marine Ecology; Renewable Energy; Microbiology; Plant Biotechnology